Erasmus and the Age of Reformation - Huizinga, Johan, 1872-1945 (Book collections on Project MUSE., 1984)
Johan Huizinga had a special sympathy for the complex, withdrawn personality of Erasmus and for his advocacy of intellectual and spiritual balance in a quarrelsome age. This biography is a classic work on the sixteenth-century scholar/humanist. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.